Features and results of treatment of rotationally unstable pelvic injuries of the «open book» type - Ankin, Mykola; Petryk, Taras; Ladyka, Viktoriia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The treatment of pelvic bones injuries is one of the most difficult problems in traumatology. Objective: to analyze the results of surgical treatment of patients with pelvic fractures of the «open book» type and to determine the most effective methods of its stabilization. Methods: a retrospective analysis of the results of treatment of 61 patients with «open book» type pelvic fractures (age from 16 to 64 years) in two groups was carried out. Patients of the first group (24 patients, 39.3 %) were made osteosynthesis the anterior part of the pelvic bones only with an external fixation device — 20 and with a plate — 4. In the second group (37 patients, 60.7 %), anterior and posterior osteosynthesis was made. To assess fractures, the Tile classification with the additions of AO was used. X-rays and CT of the pelvic bones was used in all cases. Fractures of type B1.1 were detected in 32 (52.5 %) cases, B1.2 — 29 (47.5 %). Surgery was planned according to the developed local protocol. The results were analyzed according to the system of functional assessment S. A. Majed. The follow-up period was from 6 to 12 months after the surgery. Results: early complications were found in 4 (6.5 %) patients: infection — 3, secondary displacement of bone fragments — 1. There was no significant difference between the groups in terms of treatment outcomes. Conclusions: in case of pelvic injury as an «open book», accurate diagnosis of injuries with assessment of sacroiliac connection using x-ray of the pelvis in three planes and CT are important. In case of injuries of type B1 and differences in the pubic joint up to 2.5 cm, conservative treatment is recommended, more than 2.5 cm — internal fixation of the anterior section by one or two plates, and in the case of suspected injury of sacroiliac joint, additional fixation of the sacroiliac joint with ileosacral screws.